THE LINGUISTIC FORMS OF ENGLISH SEXUAL EUPHEMISTIC EXPRESSIONS IN “LADY CHATTERLEY’S LOVERS” - Nurdina, Ovira (Universitas Gunadarma, 2017)
Sex is something that is taboo to discuss. It will make the listener and speaker who are the participants of a conversation will feel embarrassed. Euphemisms are used to replace those words considered taboo. As a part of language, euphemisms has its own linguistics forms. Using Warren’s model of linguistic forms of euphemisms, this study tries to find out the forms of sexual euphemistic expression that exist in novel Lady Chatterley’s Lover by D.H Lawrence. This study is a descriptive qualitative study. The result of the study shows that From 50 euphemistic expressions found in the novel, there 14 data included into implication, 11 data into metaphors, 7 data into particularization, 5 into metonymy, 5 into derivation, 3 into compounding, 4 into French, and 1 into Latin. Keywords: English, Euphemism, Linguistic form, Sex, Warren